Adenocarcinoma of the Stomach and Esophagus and Drinking Water and Dietary Sources of Nitrate and Nitrite - Ward, Mary H. (2008)
We conducted a population-based case-control study of adenocarcinoma of the stomach and esophagus in Nebraska, U.S.A. Nitrate concentrations in public drinking water supplies were linked to residential water source histories. Among those using private wells at the time of the interview, we measured nitrate levels in water samples from wells. Dietary nitrate and nitrite were estimated from a food-frequency questionnaire. Among those who primarily used public water supplies (79 distal stomach, 84 esophagus, 321 controls), average nitrate levels were not associated with risk (highest versus lowest quartile: stomach OR=1.2, 95% CI [0.5–2.7]; esophagus OR=1.3, 95% CI [0.6–3.1]). We observed the highest ORs for distal stomach cancer among those with higher water nitrate ingestion and higher intake of processed meat compared with low intakes of both; however, the test for positive interaction was not significant (p=0.213). We did not observe this pattern for esophagus cancer. Increasing intake of nitrate and nitrite from animal sources was associated with elevated ORs for stomach cancer and with a significant positive trend in risk of esophagus cancer (P-trend=0.325 and 0.015, respectively). Larger studies with higher exposures to drinking water sources of nitrate are warranted to further evaluate N-nitroso compound precursors as risk factors for these cancers.